REQUIREMENT FOR ORTHOPEDIC DENTAL CARE OF ADULT URBAN POPULATION OF THE REPUBLIC OF UZBEKISTAN - Sanakulov Jamshed Obloberdiyevich; Kamolov Azizjon; Mamirov Mirjalol; Murodkulov Samandar; Norjigitov Hasan (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Mass dental examinations of the adult population of the Republic of Uzbekistan were conducted. 3 age groups were examined: People living in the city of Tashkent were selected for the study: middle (45-59 years old), elderly (60-79 years old) and senile (80 years and older). The studied individuals were found to have a high loss of teeth, which is 79.3% of the urban and urban population. The most common dental defects are found in the elderly age group 59.4%, and in older people 30.9%. A high frequency of complete absence of teeth was revealed in the elderly 24.2%, and in the senile 48.0%. The results of the dental examination require improvement of orthopedic dental care in Republic of Uzbekistan.